Potential Extract Curcuma (Curcuma xanthorrizal, Roxb) as Antibacterials - Dermawaty, Dessy Eva (Majority, 2015)
Abstract Infectious diseases such as diarrhea or respiratory and digestive tract disorders is one of the biggest causes of death in the world are caused by microbial pathogens. Curcuma widely used as an antimicrobial for the content of the active compound is able to prevent the growth of microbes. Curcuma is also likely as a cure infections caused by microbial pathogens such as C. albicans, S. aureus, E. coli, B. cereus and S. mutans. The content in ginger contains chemical compounds that have active ingredients, namely kurkuminoid and essential oils. The content kurkuminoid in ginger act as anti-bacterial, anti-cancer, anti-tumor, and contains antioxidants. The content kurkuminoid in the range 1-2% of ginger and turmeric contains oil in the range of 3-12%. Curcuma categorized very powerful in inhibiting the growth of bacteria E. coli (31.56 mm) because it exceeds the standard category is very strong inhibition of ≥20 mm and a strong say in inhibiting S. aureus (15.75 mm) and C. albicans (13, 07 mm) with a strong inhibition of the standard categories of 10-20 mm. Power resistor formed other Curcuma range 8-11 mm it is considered moderate (S) (5-10 mm). Activity xanthorizol active compounds can inhibit the growth and development of the bacterium Streptococcus mutans. Xanthorizol active compound also has antimicrobial properties. Keywords: anti-bacterial, curcuminoid, Curcuma xanthorizol, essential oils Abstrak Penyakit infeksi seperti saluran pernafasan dan diare atau gangguan saluran pencernaan merupakan salah satu penyebab kematian terbesar di dunia disebabkan oleh mikroba patogen. Curcuma banyak dimanfaatkan sebagai antimikroba karena kandungan senyawa aktifnya mampu mencegah pertumbuhan mikroba. Curcuma juga berpeluang sebagai obat infeksi yang disebabkan oleh mikroba patogen seperti C. albicans, S. aureus, E. coli, B. cereus dan S. mutans. Kandungan dalam temulawak berisi senyawa-senyawa kimia yang memiliki kandungan aktif, yaitu kurkuminoid dan minyak atsiri. Kandungan kurkuminoid dalam temulawak berfungsi sebagai anti-bakteria, anti-kanker, anti-tumor, serta mengandung antioksidan. Kandungan kurkuminoid dalam temulawak berkisar 1-2% dan kandungan minyak atsiri dalam temulawak berkisar 3-12%. Segar rimpang temulawak dikategorikan sangat kuat dalam menghambat pertumbuhan bakteri E. coli (31,56 mm) karena melebihi standar kategori daya hambat sangat kuat yaitu ≥20 mm dan dikatakan kuat dalam menghambat S. aureus (15,75 mm) dan C. albicans (13,07 mm) dengan standar kategori daya hambat kuat sebesar 10-20 mm. Daya hambat yang dibentuk Curcuma lainnya berkisar 8-11 mm hal ini dikategorikan sedang (S) (5-10 mm). Aktivitas senyawa aktif xanthorizol dapat menghambat pertumbuhan dan perkembangan bakteri Streptococcus mutans. Senyawa aktif xanthorizol juga memiliki sifat sebagai antimikroba.